(3GdGUhd GdYdejI h GdYedjIs - (3ZGdH YhV(B, (3GdQaGYjs ((3YeGf(B:s (3OGQ GdjGRhQj(B,s, 2010)
(3GdeYGOdI GdeMGSHjI h JWHjbGJgG, JSLjd GdYedjGJ GdeMGSHjI , GdJShjGJ GdLQOjI , GdOhQI GdeMGSHjI , GdeYGdLI GdeMGSHjI dYedjGJ GdHVGYI (B.s
(3eQGLY U(B.223s
Keywords: (3GdEOGQI GdeGdjIs; (3GdeGdjI(B- (3GdeMGSHIs; (3GdeMGSHIs